FORMATION OF PROFESSIONAL COMPETENCE OF PUPILS AS A BASIS FOR QUALITY TRAINING UNIVERSITY GRADUATES - D. Bottaeva (Вестник университета)
The article is devoted to improving the quality of preparation of graduates of higher education institutions based on the implementation of the competence approach. The article presents the basic methods of implementation of this approach in the education system, and also considered factors influence the effectiveness of the competency approach to training of qualified graduates. Particular attention is paid to the need to bring the competences of students in line with the demands of employers in the changing conditions of the modern labor market. Based on the identified problems in the education system provides recommendations to improve the quality of university graduates with the competence approach.